Mathematical models and informational technologies of innovative project arrangement in the stakeholders’ system - Petrova, Roksana Vadimovna; Liubicheva, Olga Igorivna; Morozova, Anna Ivanovna (НТУ "ХПІ", 2019)
During the involvement of innovative projects into knowledge-intensive high-tech enterprises, the process of creating a system of interested stakeholder management becomes vital. The given work contains the results of conducted analysis concerning the problem of innovative potential management of high-tech enterprises. The necessity of the analysis of informational technologies in the conditions of the non-equilibrium economy is considered. Various models of project management in the system of stakeholders are presented in the work. The stages of Nicholas model are considered. A mathematical model is proposed for the management and investors of the project, in terms of maximizing profits under specified constraints.

При залученні інноваційного проекту в наукомісткі високотехнологічні підприємства актуальним процесом стає створення системи управління зацікавленими учасниками. Проведено аналіз проблеми управління інноваційним потенціалом наукомістких підприємств. Розглянуто необхідність аналізу інформаційних технологій в умовах нерівноважної економіки. Розглянуто різні моделі управління проектами в системі зацікавлених осіб. Розглянуто етапи використання моделі Ніколаса. Запропоновано математичну модель для керівництва та інвесторів проекту, в умовах максимізації прибутку при заданих обмеженнях.
Математичні моделі і інформаційні технології організації інноваційних проектів у системі стейкхолдерів
Keywords: Mitchell’s model; ASC model; innovative projects; модель Мітчелла; інформаційні технології